White matter hyperintensity burden predicts cognitive but not motor decline in Parkinson's disease: results from the Ontario Neurodegenerative Diseases Research Initiative. (14th February 2023) - Carvalho de Abreu, Daniela Cristina; Pieruccini‐Faria, Frederico; Sarquis‐Adamson, Yanina; Black, Alanna; Fraser, Julia; Van Ooteghem, Karen; Cornish, Benjamin; Grimes, David; Jog, Mandar; Masellis, Mario; Steeves, Thomas; Nanayakkara, Nuwan; et al.
Abstract: Background and purpose: The pathophysiology of Parkinson's disease (PD) negatively affects brain network connectivity, and in the presence of brain white matter hyperintensities (WMHs) cognitive and motor impairments seem to be aggravated. However, the role of WMHs in predicting accelerating symptom worsening remains controversial. The objective was to investigate whether location and segmental brain WMH burden at baseline predict cognitive and motor declines in PD after 2 years. Methods: Ninety‐eight older adults followed longitudinally from Ontario Neurodegenerative Diseases Research Initiative with PD of 3–8 years in duration were included. Percentages of WMH volumes at baseline were calculated by location (deep and periventricular) and by brain region (frontal, temporal, parietal, occipital lobes and basal ganglia + thalamus). Cognitive and motor changes were assessed from baseline to 2‐year follow‐up. Specifically, global cognition, attention, executive function, memory, visuospatial abilities and language were assessed as were motor symptoms evaluated using the Movement Disorder Society Unified Parkinson's Disease Rating Scale Part III, spatial–temporal gait variables, Freezing of Gait Questionnaire and Activities Specific Balance Confidence Scale. Results: Regression analysis adjusted for potential confounders showed that total and periventricular WMHs at baseline predicted decline in global cognition ( p < 0.05). Also, total WMH burden predicted the decline of executive function ( p < 0.05). Occipital WMH volumes also predicted decline in global cognition, visuomotor attention and visuospatial memory declines ( p < 0.05). WMH volumes at baseline did not predict motor decline. Conclusion: White matter hyperintensity burden at baseline predicted cognitive but not motor decline in early to mid‐stage PD. The motor decline observed after 2 years in these older adults with PD is probably related to the primary neurodegenerative process than comorbid white matter pathology.